Integration of Non-Targeted Metabolomics and Targeted Quantitative Analysis to Elucidate the Synergistic Antidepressant Effect of Bupleurum Chinense DC-Paeonia Lactiflora Pall Herb Pair by Regulating Purine Metabolism - Jiajun Chen; Jiajun Chen; Jiajun Chen; Tian Li; Tian Li; Tian Li; Xuemei Qin; Xuemei Qin; Xuemei Qin; Guanhua Du; Guanhua Du; Yuzhi Zhou; et al. (Frontiers Media S.A., 2022)
Graphical Abstract